Impact of clinical simulation on nursing learning in critical care (Research, Society and Development, 2022)
The learning process comes from the integration of the student's previous knowledge, acquired through their ability to receive new information. One of the ways of building knowledge is the Active Teaching Methodologies, such as clinical simulation, in which the subject is the protagonist during learning. The objective of this study is to evaluate the integration between clinical simulation and learning in nursing in Critical Care. This is an integrative review with a qualitative approach and a descriptive nature. Data collection was carried out in the following databases: National Library of Medicine (PubMed), Virtual Health Library (VHL) and Embase, and took place from March to May 2022. After filtering, reading the titles and abstracts, reading the articles in full and excluding those that did not comply with the research objectives or were duplicates, 20 publications were selected because they were of relevance to this review. The use of clinical simulation aimed at care in critically ill patients has been frequently applied, both in the continuing education of nursing teams at the national level and in other countries, as well as in education in institutions that offer undergraduate and graduate degrees in nursing, increasing the capacity for self-perception, communication and, therefore, improving the behaviour of professionals providing nursing care. Clinical simulation has been shown to be an effective instrument in the improvement of nursing students and professionals, leveraging the teaching of Nursing in critical care, providing subsidies for learning.